Biodiversidade da vegetação de mata atlântica na trilha do rio Paraibuna - Parque Estadual da Serra do Mar - Marmontel, Caio Vinicius Ferreira [UNESP]; Rodrigues, Valdemir Antonio [UNESP] (Revista Scientia Agraria Paranaensis (SAP), 2013)
This study aimed to characterize the floristic composition of the arboreous vegetation of the Atlantic Forest in the trail of Paraibuna river belonging to the Section Cunha of the Serra do Mar State Park. Ten plots measuring 25 m² each were marked and all woody tree species with DBH greater than or equal 5 cm were recorded. In the survey of native tree species, we sampled 90 live individuals, distributed in 19 botanical families, 26 genera and 28 species identified, presenting a diameter class according to the standards of native forests. The results were as follows: Myrtaceae was the most abundant family; the species Cyathea delgadii and Nectandra lanceolata had the highest number of individuals; the most representative successional group consisted of the secondary species; in seed dispersal syndrome, zoochory was the method with the highest abundance, reaching 60% and providing diversity index of 3.01. Studies of this nature are of great importance concerning the Atlantic Forest biome, since they provide theoretical basis to support any initiatives for protection, restoration and recovery of other areas with similar characteristics, serving, therefore, as a model.

Este trabalho objetivou a caracterização florística da vegetação arbórea de Mata Atlântica na Trilha do Rio Paraibuna, pertencente ao Núcleo Cunha do Parque Estadual da Serra do Mar. Foram marcadas 10 parcelas com dimensão de 25 m² cada uma e registradas todas as espécies arbóreas lenhosas com DAP maior ou igual a 5 cm. No levantamento das espécies arbóreas nativas, foram amostrados 90 indivíduos vivos, distribuídos em 19 famílias botânicas, 26 gêneros e 28 espécies identificadas, apresentando a classe diamétrica no padrão de florestas nativas. Os resultados foram os seguintes: a família com maior abundância foi a Myrtaceae; as espécies com maior número de indivíduos foram Cyathea delgadii e Nectandra lanceolata; o grupo sucessional mais representativo foi constituído das espécies secundárias; na síndrome de dispersão das sementes, o método que apresentou maior abundância foi a zoocoria, atingindo 60% e proporcionando índice de diversidade de 3,01. Estudos dessa natureza são de grande importância se tratando do bioma Mata Atlântica, formando bases teóricas para subsidiar quaisquer iniciativas voltadas para a proteção, restauração e recuperação de outras áreas com características semelhantes, servindo como modelo.
Biodiversity of Atlantic Forest vegetation in the trail of Paraibuna river - Serra do Mar State Park
Keywords: Floristic composition; Diversity; Araucaria forest; Ombrophilous dense forest; Composição florística; Diversidade; Floresta de araucária; Floresta ombrófila densa